The Influence of Work Experience, Auditor Expertise, and Time Pressure on Audit Quality with Ethics as an Intervening Variable - Achmad , Fadly; Rahman, Abdul; ., Arifuddin; Bandang, Agus; ., Haryanto (Journal of Ecohumanism, 2025)
The surge in financial scandals following the global financial crisis and the collapse of major corporations (such as Enron, WorldCom, and Parmalat) has prompted market demands for high audit quality standards. High audit quality requires the crucial role of auditors in providing information regarding financial statements and market trends, which assist information users (creditors and investors) in their decision-making processes. This study aims to analyze factors that can enhance audit quality by considering work experience, auditor expertise, and time pressure as predictor variables, as well as the mediating role of ethics. Data were collected through questionnaires distributed to auditors of the Local Government Inspectorate of Regencies in South Sulawesi. The sample size was determined using the Slovin method, resulting in 77 respondents. Data were then analyzed using the Structural Equation Modeling (SEM) method with SmartPLS 4.09. The findings indicate a positive and significant influence of work experience and auditor expertise on audit quality, while time pressure negatively impacts audit quality. Ethics serve as a significant mediating variable that influences the relationship between work experience and auditor expertise on audit quality, and mitigates the negative impact of time pressure on auditor behavior that may diminish audit quality. This study contributes to the practice of ethical codes within the Inspectorate of Regencies/Cities in South Sulawesi. A strong commitment to the ethical code will guide auditors in avoiding behaviors that reduce audit quality, thereby emphasizing the need for building an ethical culture to guide auditors' ethical behavior.